2008
DOI: 10.2967/jnumed.107.047118
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Examination Method for the Diagnosis of Misery Perfusion with Count-Based Oxygen Extraction Fraction Elevation in 15O-Gas PET

Abstract: 15 O-Gas PET is useful for evaluating hemodynamic status in patients with ischemic cerebrovascular disease. To reduce examination time and exposure to radioactive gas, we assessed a count-based method with shorter continuous 15 O 2 gas inhalation. Methods: Twenty-five patients (66 6 13 [mean 6 SD] y old) with unilateral cerebrovascular stenoocclusive disease were examined by use of measurements of asymmetric oxygen extraction fraction (OEF) elevation. Dynamic PET scans of 1 min per frame were obtained starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…A normalized method using cerebellar counts showed poor agreement with quantitative OEF elevation [72]. However, another study employing a simplified AI comparison method using count-based ratio images showed good accordance with the AI of quantitative OEF in CVD patients [73,74]. The advantage of these simplified methods is that the scanning protocol is simple and the operation is non-invasive without arterial blood sampling.…”
Section: Review Of Clinical Studiesmentioning
confidence: 93%
“…A normalized method using cerebellar counts showed poor agreement with quantitative OEF elevation [72]. However, another study employing a simplified AI comparison method using count-based ratio images showed good accordance with the AI of quantitative OEF in CVD patients [73,74]. The advantage of these simplified methods is that the scanning protocol is simple and the operation is non-invasive without arterial blood sampling.…”
Section: Review Of Clinical Studiesmentioning
confidence: 93%
“…Kobayashi et al [25] reported the cbOEF-AI can be successfully used to diagnose misery perfusion if one uses 4-7 min of the summation time for continuous inhalation of 15 15 O data. Hence, the total study time for their study should be longer than 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…By the cbOEF image, one can non-invasively evaluate asymmetric increase in OEF value with a simple calculation [6,21,22,24]. Recently, Kobayashi et al investigated the optimal scan protocol for computing cbOEF to diagnose misery perfusion [25]. They concluded the cbOEF could appropriately diagnose misery perfusion when they used 15 2 15 O was utilized for the administration of tracers.…”
Section: Introductionmentioning
confidence: 98%
“…Kobayashi et al [21] examined relationship between count-based OEF and scan duration. They used quantitative OEF as a standard to evaluate optimal scan duration.…”
Section: Tissue Heterogeneitymentioning
confidence: 99%